Evaluation of Coffea arabica Cultivars for Resistance to Meloidogyne konaensis - Roxana Myers; Cathy Mello; Chifumi Nagai; Brent Sipes; Tracie Matsumoto (Agriculture, 2023)
Coffee is an important agricultural crop for the State of Hawaii. Developing new coffee cultivars with resistance to damaging pests and diseases is crucial for improving production and maintaining the profitability of the industry. With the recent discovery of Hemileia vastatrix, coffee leaf rust (CLR), to Hawaii there is a strong interest in replanting with CLR-resistant germplasm. However, when selecting an appropriate cultivar for replanting, susceptibility to other pathogens, such as plant-parasitic nematodes, should be taken into consideration. Meloidogyne konaensis, the Kona coffee root-knot nematode, causes severe destruction of the root system, reducing the yield and causing the mortality of susceptible Coffea arabica cv. Typica trees. Fortunately, resistance to root-knot nematodes has been found in some C. arabica germplasm. In this study, accessions of wild Ethiopian C. arabica and two CLR-resistant C. arabica cultivars, Tupi-HI and Obata, were evaluated for resistance to M. konaensis in a greenhouse bioassay. All Ethiopian accessions retained high levels of resistance, resulting in reproductive factors (Rfs) lower than 1.0, and low root-rot ratings. Tupi-HI was highly susceptible to M. konanensis, with an Rf value of 7.12, whereas Obata was slightly susceptible, with an Rf value of 2.33. Both cultivars had high root-rot ratings, suggesting intolerance to the nematode. Hybridizing Ethiopian C. arabica with Tupi-HI or Obata may result in new elite cultivars, resistant to both H. vastatrix and M. konaensis.